2009
DOI: 10.1016/j.electacta.2009.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Ag and Pd on a reconstructed Au(1 1 1) electrode surface studied by in situ scanning tunneling microscopy

Abstract: Electrochemical deposition of Ag and potential-induced structural change of the deposited Ag layer on a 23 3  reconstructed surface of Au (111)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
(37 reference statements)
2
7
0
Order By: Relevance
“…Noticeably, at the low coverage of particles forming under the tip, we can observe a distinct preference for specific nucleation sites. As this deposition took place on a reconstructed Au(111) surface, we attribute the line order to the presence of elbow sites of the herringbone structure where nucleation is favored, as reported for UHV vapor deposited [49,50] or electrochemically deposited Pd particles on reconstructed Au(111) [27] . The preference for defect sites and steps after hydrogen preconditioning underlines a considerable mobility of the particles forming in the deposition process, in line with the observed tendency to aggregate.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…Noticeably, at the low coverage of particles forming under the tip, we can observe a distinct preference for specific nucleation sites. As this deposition took place on a reconstructed Au(111) surface, we attribute the line order to the presence of elbow sites of the herringbone structure where nucleation is favored, as reported for UHV vapor deposited [49,50] or electrochemically deposited Pd particles on reconstructed Au(111) [27] . The preference for defect sites and steps after hydrogen preconditioning underlines a considerable mobility of the particles forming in the deposition process, in line with the observed tendency to aggregate.…”
Section: Resultssupporting
confidence: 74%
“…This is in line with an expected epitaxial growth, as seen in most previous studies, [26,33] except for the very slow deposition in highly dilute electrolytes on the reconstructed surface by Uosaki et al, in which 3D particles up to three layers high have been found. [27] Note that different tip radii might slightly influence the observed area, but not the observed height distributions.…”
Section: Resulting Particle Morphology and Dispersionmentioning
confidence: 97%
See 2 more Smart Citations
“…The STM tip was a simply cut tungsten wire, of which the top was electrochemically sharpened in 0.6 M KOH, then insulated with nail polish. 54,55 All the STM images were obtained in the constant current mode (I tip : 0.30 nA, V sample : 0.30 V). Ex situ STM observation of the TMMPP SAM on the Au(111) was carried out in ultrapure water.…”
Section: Stm Measurementsmentioning
confidence: 99%